1973
DOI: 10.1021/j100623a007
|View full text |Cite
|
Sign up to set email alerts
|

g Factor and hyperfine coupling anisotropy in the electron spin resonance spectra of methyl-, ethyl-, and allyl- type radicals adsorbed on silica gel

Abstract: These data suggest that at 77 K the methyl radicals rotate about an axis perpendicular to the planes of the radical, whereas the ethyl radical rotates about the C-C bond axis. The analysis of spectra from allyl and methallyl radicals is less conclusive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

1976
1976
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 1 publication
4
32
0
Order By: Relevance
“…Small discrepancies in the reproduction of the spectrum can be understood considering that couplings due to H(5) and H(6) are not compatible with an alkyl radical and indicate that even though these radicals are largely dominant, other radicals are formed in the irradiated polymer. Comparison of H(5) and H(6) couplings with literature values indicates that these are consistent with allyl radicals, which are assumed to be formed as a minor fraction during the irradiation process . Even though ENDOR and HYSCORE signal intensities cannot in general be used for quantization of the number of species, the relative intensities of the allyl proton with respect to the alkyl proton signals indicate at least an order of magnitude difference in the number of the two species.…”
Section: Resultsmentioning
confidence: 99%
“…Small discrepancies in the reproduction of the spectrum can be understood considering that couplings due to H(5) and H(6) are not compatible with an alkyl radical and indicate that even though these radicals are largely dominant, other radicals are formed in the irradiated polymer. Comparison of H(5) and H(6) couplings with literature values indicates that these are consistent with allyl radicals, which are assumed to be formed as a minor fraction during the irradiation process . Even though ENDOR and HYSCORE signal intensities cannot in general be used for quantization of the number of species, the relative intensities of the allyl proton with respect to the alkyl proton signals indicate at least an order of magnitude difference in the number of the two species.…”
Section: Resultsmentioning
confidence: 99%
“…24͒ usually discuss END contributions to spin relaxation and linewidths in terms of anisotropies, both ␦A and ␦g. While anisotropy in the g tensor can be important in high-field ESR, g anisotropy is small for alkyl radicals 63 ͑for ethyl, ␦gՇ0.0004 [64][65][66] ͒ so that e ␦g/gӶ␦A for the conditions of our experiments, and can be ignored. The isotropic part of the hyperfine interaction can also contribute to spin relaxation if it is modulated at an appropriate frequency.…”
Section: Interpretation Of the Parametersmentioning
confidence: 99%
“…zeolites, alumina, aluminosilicalites or higher-order oxides are attractive materials in numerous applications in catalysis. Previous research has shown that those materials play a significant role in the separation and stabilization of various reactive intermediates as atoms, radicals, radical ions, and clusters [1][2][3][4][5][6][7]. Studies of such intermediates are very important for a better understanding of the mechanisms of chemical reactions in polymerization, heterogeneous catalysis, photochemistry, and radiation chemistry and biology.…”
Section: Introductionmentioning
confidence: 99%
“…Amorphous silica is one of the most common supports in catalysis and was the subject of several experimental studies during the past decades [4,5,24]. Silica gel support systems are widely used in studies of transition metal ions or complexes [25] and are successfully applied in controlled polymerization [26] and in studies of ionic radicals [27,28].…”
Section: Introductionmentioning
confidence: 99%